Pacing: A Concept Analysis of a Chronic Pain Intervention. (2013) - Jamieson-Lega, Kathryn; Berry, Robyn; Brown, Cary A
Abstract : BACKGROUND: The intervention of pacing is regularly recommended for chronic pain patients. However, pacing is poorly defined and appears to be interpreted in varying, potentially contradictory manners within the field of chronic pain. This conceptual lack of clarity has implications for effective service delivery and for researchers' ability to conduct rigorous study. An examination of the background literature demonstrates that while pacing is often one part of a multidisciplinary pain management program, outcome research is hindered by a lack of a clear and shared definition of this currently ill-defined construct. OBJECTIVES: To conduct a formal concept analysis of the term 'pacing'. METHODS: A standardized concept analysis process (including literature scoping to identify all uses of the concept, analysis to determine defining attributes of the concept and identification of model, borderline and contrary cases) was used to determine what the concept of pacing does and does not represent within the current evidence base. RESULTS: A conceptual model including the core attributes of action, time, balance, learning and self-management emerged. From these attributes, an evidence-based definition for pacing was composed and distributed to stakeholders for review. After consideration of stakeholder feedback, the emergent definition of pacing was finalized as follows: "Pacing is an active self-management strategy whereby individuals learn to balance time spent on activity and rest for the purpose of achieving increased function and participation in meaningful activities". CONCLUSION: The findings of the present concept analysis will help to standardize the use and definition of the term pacing across disciplines for the purposes of both pain management and research.